To what extent did Cubans support Fulgencio Batista's coup d'etat in March 1952 - Kiteley, Robert G. (2013)
There was no more exciting place to be on January 1 1959 than Havana, Cuba. It was the defining moment in the life of a nation, when all that came before it seemed to be a prelude. Fidel Castro led a revolution which had captivated an entire population and had swept a brutal tyrant from power. In the emotive moment of revolution, and, the significance of what happened next, an objective portrayal of Fulgencio Batista y Zaldívar has somehow been lost to the annals of history. This thesis explores the extent to which Cubans supported or opposed Batista as he took power and discarded of the Cuban democratic system in March 1952.